1998
DOI: 10.1074/jbc.273.41.26289
|View full text |Cite
|
Sign up to set email alerts
|

The Non-histone Chromatin Protein HMG1 Protects Linker DNA on the Side Opposite to That Protected by Linker Histones

Abstract: Linker histones and HMG1/2 constitute the two major proteins that bind to linker DNA in chromatin. While the location of linker histones on the nucleosome has attracted considerable research effort, only a few studies have addressed the location of HMG1 in the particles. In this study, we use a procedure based on micrococcal nuclease digestion of reconstituted nucleosomal particles to which HMG1 has been bound, followed by analysis of the protected DNA by restriction nuclease digestion, to locate the HMG1 bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…These proteins share many features of DNA-binding behavior, although they are structurally unrelated (Zlatanova and van Holde, 1998b). An early study indicated that HMGB1 protects linker DNA on the side opposite to that protected by linker histones (An et al, 1998). We now know that they have opposing effects on nucleosome assembly and stability (Paull et al, 1993).…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…These proteins share many features of DNA-binding behavior, although they are structurally unrelated (Zlatanova and van Holde, 1998b). An early study indicated that HMGB1 protects linker DNA on the side opposite to that protected by linker histones (An et al, 1998). We now know that they have opposing effects on nucleosome assembly and stability (Paull et al, 1993).…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…Histone H1 binds linker DNA where it enters and exits the nucleosome ( Fig. 2) (23)(24)(25)(26). Unlike core histones, which have residency times on a time scale of hours, linker histones are quite mobile, with residency times being measured in minutes (16,27,28).…”
Section: Linker Histonesmentioning
confidence: 99%
“…Competition between HMGB1/-B2 proteins and linker histones for four-way junctions and cisplatin-modified DNA has been clearly demonstrated [41, 42]. Although their organization in isolated nucleosomes or in chromatin is not fully understood, HMGB1/B2 seems to preferentially bind to linker DNA at the entry/exit of nucleosomes, next to the nucleosome dyad axis [43, 44]. Since these are also major sites of H1-nucleosome interaction it is likely that this positional overlap plays an important role in the HMGB-H1 interplay in chromatin.…”
Section: Hmg-h1 Interactionsmentioning
confidence: 99%